Artificial Intelligence and Hospitals-Healing with Algorithms: Turning Potential into Patient Benefit-The Future of Hospital Medicine - Gautam, Mani Prasad (Journal of Bharatpur Hospital, 2025)
Artificial intelligence (AI) is rapidly transitioning from experimental tools to real-world clinical deployment. Hospitals now face the challenge of translating AI’s promise into tangible patient benefit. This editorial discusses current evidence, risks, and best practices in the integration of AI into hospital workflows-highlighting lessons from sepsis prediction, acute kidney injury forecasting, and imaging diagnostics. It argues that successful implementation depends not only on technical performance but also on usability, transparency, and equity. For resource-constrained public hospitals such as Bharatpur Hospital, the path forward lies in thoughtful prioritization, strong clinical–data partnerships, and vigilant monitoring.